Peran Sikap, Risiko, dan Kebijakan Pemerintah dalam Mendorong Niat Pembelian Mobil Listrik di Kota Palembang - Armanto, Rully; Rasjid, Abdullah; Gunarto, Muji (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to analyze the influence of attitude, risk perception, and government policy on the intention to purchase electric cars in Palembang City. Referring to the Stimulus-Organism-Response (SOR) theoretical framework, this study posits that risk perception and policy serve as a stimulus, attitude as an organism, and purchase intention as a response. This study uses a quantitative approach with a survey method on 135 respondents who have the potential to be electric car buyers. The results of the study indicate that risk perception does not have a significant effect on attitude or purchase intention. In contrast, government policy and environmental concerns have a significant positive effect on attitude, while relative advantage also has a strong contribution. Consumer attitudes have been shown to have a significant effect on forming the intention to purchase electric cars. The conclusion of this study confirms that the strategy for adopting electric cars needs to be focused on strengthening positive consumer attitudes through policy incentives, environmental education, and promotion of the benefits of electric vehicles. Managerially, the government needs to expand fiscal and non-fiscal policies and accelerate the development of supporting infrastructure. Manufacturers and automotive industry players are also expected to increase marketing campaigns based on environmental values ​​and operational efficiency to increase the attractiveness of the electric vehicle market.